Intra‐articular hip neurofibromas in von Recklinghausen's disease. Issue 9 (22nd September 2021) - Lassoued Ferjani, Hanene; Moalla, Myriam; Maatallah, Kaouther; Ben Nessib, Dorra; Triki, Wafa; Kaffel, Dhia; Hamdi, Wafa
Abstract: Neurofibromatosis is a genetic disorder with osteo‐articular manifestations. The intra‐articular location of neurofibroma is scarce. Abstract : Neurofibromatosis is a genetic disorder with osteo‐articular manifestations. The intra‐articular location of neurofibroma is scarce.